Immaterial Cost and Production: Maximum Production Cost Level Through Marginal Approach - Nur Umaima Wafia; Reni Furwanti; Dini Maulana Lestari (el-Jizya: Jurnal Ekonomi Islam, 2020)
This paper will discuss about the immaterial costs and production yields at one of the refined sugar factory companies in Makassar, South Sulawesi. The theory is based on the fact that Immaterial is a cost that is almsgiving, meaning costs that are outside of the basic costs of the company in producing production, so this research aims to find out: (1) what is the production cost needed to produce this production, (2) the maximum level of production at company from 2013 to 2017. This type of research is a quantitative study because it uses a questionnaire in the form of values ​​that are processed using the marginal cost approach formula. The results of the analysis show that (1) the maximum level of production costs occurred in 2016 amounting to 6,912 with an Immaterial cost of Rp. 2,481,796,800 and the total production produced is 359,077.3 tons (2) The required workforce with the total production produced is 359,077.3 tones of 180 people including the maximum production point which means that the lowest value is achieved (optimal).